Rare Fit on Ankle Dermatofibrosarcoma Protuberans - Güzelyüz, Betül; Pekmezci, Yasemin; Demiröz, Anıl; Pekmezci, Salih (Cerrahpaşa Medical Journal, 2023)
Dermatofibrosarcoma protuberans is a rare, slow-growing mesenchymal tumor of soft tissue with low-to-moderate malignancy potential, high local recurrence, and low distant metastatic activity. Although it is frequently seen in the trunk and proximal upper extremities and head and neck region, there are a few cases in the literature in localizations such as lower extremities and breasts. Therefore, it is not among the first diagnoses that come to mind in lower extremity lesions and is diagnosed after histopathological examination. In this case, a 41-year-old female patient who had thought to be a callus on the posteromedial left ankle for approximately 3 years and therefore neglected was reported as having low-grade dermatofibrosarcoma protuberens after excision and had a suspicious lesion in the left breast for the same diagnosis on detailed examination. Cite this article as: Güzelyüz B, Pekmezci Y, Demiröz A, Pekmezci S. Rare fit on ankle dermatofibrosarcoma protuberans. Cerrahpaşa Med J. 2023;47(2):241-242.